Determinantes sociales e índices de la malnutrición de niños de la parroquia de Simiatug, Guaranda en el periodo 2022. - Yumbo Moposita, Jerman Walter (2023)
In the present investigation I will deal with the social determinants and indices of malnutrition of children in the parish of Simiatug, in the same way the percentage of malnutrition will be verified, since poor nutrition has changed the lives of human beings, the Nutritious food has been lost for many years now, globally, nationally and locally. The social classes are related to the existing life, the place where they live, customs, own and socioeconomic actions. One of the consequences that most affects this parish is the economy, since families suffer from food due to lack of money, which is why children do not have a good development in their childhood stage, to verify malnutrition in children, it is necessary to take Taking into account age, weight and height, with this we can demonstrate the result of malnutrition in children, if they do not have a good diet, the development of the child is delayed quickly, the faster they have a good diet, the better their physical development. , the parish of Simiatug, has a high level of malnutrition, so it is very necessary to treat this problem to decrease and have healthy children. In this sense, the research project has a social and theoretical approach that goes according to the quantitative research method, under these analyzes I will obtain clear and precise information to identify the index of malnutrition in children in the Simiatug parish belonging to Guaranda city.